2022
DOI: 10.3390/ijms231911887
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between CXCR4/ACKR3 and EGFR Signaling in Breast Cancer Cells

Abstract: A better understanding of the complex crosstalk among key receptors and signaling pathways involved in cancer progression is needed to improve current therapies. We have investigated in cell models representative of the major subtypes of breast cancer (BC) the interplay between the chemokine CXCL12/CXCR4/ACKR3 and EGF receptor (EGFR) family signaling cascades. These cell lines display a high heterogeneity in expression profiles of CXCR4/ACKR3 chemokine receptors, with a predominant intracellular localization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Collectively, these observations are reminiscent of recent findings indicating that the EGF receptor and the HER3/HER2 receptors signal to Erk1,2 through active CXCR4/ACKR3 even in the absence of CXCL12 (Neves et al, 2022) and suggest that components of the Ephrin/Eph systems can likewise highjack the CXCR4 signaling machinery to activate the Erk1,2 pathway.…”
Section: Gai Protein Activation a Previous Study Has Demonstrated Tha...supporting
confidence: 68%
“…Collectively, these observations are reminiscent of recent findings indicating that the EGF receptor and the HER3/HER2 receptors signal to Erk1,2 through active CXCR4/ACKR3 even in the absence of CXCL12 (Neves et al, 2022) and suggest that components of the Ephrin/Eph systems can likewise highjack the CXCR4 signaling machinery to activate the Erk1,2 pathway.…”
Section: Gai Protein Activation a Previous Study Has Demonstrated Tha...supporting
confidence: 68%
“…Such results can partially be explained by the preferred localization of ACKR3 in intracellular compartments, e.g. endosomes (46,47). It has also been shown that ACKR3 surface expression in the same lymphoma cells is increased upon in vivo "conditioning" in subcutaneous grafts and further ex vivo isolation, without any modi cation in ACKR3 gene expression, again suggesting a particular tra cking of the receptor from intracellular compartments to the plasma membrane(48).…”
Section: Discussionmentioning
confidence: 99%